KELIMPAHAN DAN KEANEKARAGAMAN GASTROPODA PADA ZONA INTERTIDAL DI PULAU BANGKA BAGIAN TIMUR - Okto Supratman; Arthur Muhammad Farhaby; Jemi Ferizal; Okto Supratman (JURNAL ENGGANO)
AbstractEnvironmental damage from anthropogenic activity will lead to a decrease in water quality, which then affects aquatic organisms including Gastropoda. So it is necessary to do a study of diversity and abundance of gastropods in East Bangka Island.The study was conducted from June to December 2017. The research locations were divided into 6 stations. Data collection of gastropods using squares of size 50 cm x 50 cm, performed by direct gastropod removal by hand, then identified in Water Resource Management Laboratory. The results of this study found 12 species of gastropods from 8 families. The families found are Cerithideidae (2 species), Cerithiidae (1 species), Cirridae (1 species), Nassariidae (2 species), Neritidae (2 species), Planaxidae (1 species), Muricidae (1 Species) and Costellariidae (2 Species ). The highest abundance of gastropods is Certhidea cingulata species with an average abundance of 124.54 ind / m2. The value of diversity index of gastropod in the eastern part of the island of Bangka categorized small, it is thought to be caused by loss of habitat as a result of mining activities at sea. Keywords: Gastropods, Diversity, Abundance, Intertidal Zone